Improving Learning Independence of Elementary Students through the Two Stay Two Stray Method - Nopi Sari (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study aims to find out how much the learning independence of students increases after the application of the Two Stay Two Stray method in the learning process. The type of research is Classroom Action research. Data collection methods through in-depth observation (observation) and documentation. The research was conducted in two cycles. The results showed an increase in student learning activities, namely in the aspect of student enthusiasm increased by 49%, seriousness in paying attention to the teacher's explanation increased by 40%. The cohesiveness of discussing in groups increased by 39%, and responding to questions increased by 52%. While in the aspect of learning independence shows an increase in the indicator of critical attitude in learning there is a significant increase of 53%. Creative learning indicators increased by 42%. Indicators of having innovation in learning increased by 84%, Indicators Not affected by other groups / not cheating increased by 34%. The indicator of not asking for help from other groups in solving problems increased by 42%. And the critical thinking indicator increased significantly by 42%. So it can be concluded that this method is able to increase student learning independence